DIGITAL INDIA PROGRAM – MAIN PILLARS AND OBJECTIVE - Shukla, Rajesh Kumar; Singh, Amar Pal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article is presented to understand the purpose of Digital India program and key pillars of Digital India program where governments are paying more focus toward transforming India into a digitally empowered society and knowledge economy. This article also explains why digitalization matters and which way it is going to help the nation and what is the economic impact of digitalization in India.